ANALISIS PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS DALAM PEMBELAJARAN TEMATIK SISWA KELAS V SD NEGERI 02 CANDISARI PURWODADI - Ema Alfitasari; Qoriati Mushafanah; Sunan Baedowi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The lack of students understanding and critical thinking skills in learning occurs because the variety of learning models used by the teacher is not optimal, although basically the teacher has made several variations of the learning model but in practice the variation of the learning model carried out so far has not been able to encourage students' understanding and thinking skills. The purpose of this study was to analyze the application of the Problem Based Learning model to critical thinking skills in thematic learning of fifth grade students at SD Negeri 02 Candisari. This study uses qualitative research methods, in which researchers make observations and actions of the sources that take precedence. Data collection techniques used are observation, interviews and documentation. The results of the research show that the application of the problem-based learning method in the teaching and learning process really helps students to improve students critical thinking skills as evidenced by the student learning outcomes which have increased by 85% having completed KKM. This is because the application of the problem-based learning method makes it easier for students to understand the material taught by the teacher, makes students more active and more confident in presenting their work, and is more courageous in answering questions posed by friends between groups.